(MIS) MANAGING SOCIAL SECURITY IN THE UK: : NEOLIBERAL WARNINGS FOR BRAZIL - Souza Fraga, Vanessa; Prideaux, Simon; Vale Mendes Camões, Silvia Maria (Nomos: Revista do Programa de Pós-Graduação em Direito da UFC, 2023)
Abstract In this opinion paper, we seek to raise problems that a social security neoliberal/privatised welfare benefit system could and did face. We do so, by pointing examples from the United Kingdom (UK) to outline the problem of a free market-based dependency on the payment of welfare benefits and both private and State pensions. Beginning with the concept of neoliberalism, we examine the problems surrounding the creation and enactment of the Youth Training Scheme (1983), especially as they relate to youth employment policies from the 1980s to the ongoing but dissipating ‘Kickstart’ proposals, the geographical and situational displacement that occurred within and without the paid labour market (PLM), by an examination of the difficulties encountered by the gradual introduction of the New Deal Scheme (1998-1999) and its perverse incentive to employers, and, also, the relatively successful but short-lived Future Jobs Fund (2009) with its transference of—conditionality—from employees to employers. Through the use of Hansard Report (of all Parliamentary debates), this article is based upon the examination of past and present government Green and White papers to help substantiate how social policies evolve. More poignantly, such an examination of papers helped to reveal both the thought process behind the legislative proposals and the intent/aim of whichever government was trying to enact them. Facts and statistics were gathered from evaluation reports after such papers were passed into legislation. Independent analysis from the Office of Budget Responsibility (OBR), the Institute of Economic Affairs (IEA) and the Institute of Fiscal Studies (IFS) was gathered to give quantitative substantiation to the case at hand. By way of a supplementary analysis, independent think tanks, expert commentaries, interviews, theory, and literature reviews were also consulted to add qualitative dimensions to the factual analysis of how the situation ‘is’ and, as a consequence, provide an informed understanding and/or discussion of how the contemporary state of affairs has arisen. By doing so, the possibilities of remedying the situation are provided with a more holistic understanding of the current situation and, thus, avoiding a more isolated myopic quantitative analysis. Finally, we conclude the article with a consideration of youth training and ambitions of how lessons from the UK past can inform Brazilian policy makers to avoid the failures of yesteryear in the UK. Key words: public social security; social impact; youth unemployment.